UNSERE MÜTTER, UNSERE VÄTER (PENETRASI IDENTITAS GENDER PRIA JERMAN MELALUI WACANA KRITIS SARA MILLS) - Firda Suci Azhari; Dedi Kurnia Syah Putra (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
The use of mass media as a form of propaganda have been performed since ancient times, especially during World War II. Gender and propaganda are two things that cannot be separated. The war miniseries “Unsere Mütter, Unsere Väther” constructing a male gender identity to build the positive image of German man. This study attempts to identify how construction of gender identity man were built to the figure of Germans. This research is a discourse analysis which uses critical paradigm, through qualitatif appoarch. The analysis that is used is critical discourse analysis combine with Sara Mills methodological analysis. After the analysis is done, the regained conclusion is that “Unsere Mütter, Unsere Väther trying to presenting the positive image of German’s Army by placing a male not only as a subject (narrator) but also as an object (which is told). Placement of the audience in the film is also one of the factors, by following the dominant reading in this film then the audience is led to the position itself based on the perspective of the German army.